GENE REPLACEMENT OF MUTANT PRESENILIN1 NORMALIZES GAMMA‐SECRETASE FUNCTION IN MODELS OF AUTOSOMAL DOMINANT ALZHEIMER'S DISEASE. (20th December 2022) - Moore, Ben David; Schaeffer, Eric
Abstract: Background: Paros Bio is developing an AAV gene therapy for the treatment of Autosomal Dominant Alzheimer's Disease (ADAD), an early onset form of AD (onset at <65 years of age). ADAD is mainly caused by mutations in the presenilin 1 ( PSEN1 ) gene, which encodes the catalytic subunit of γ‐secretase complex and is responsible for the cleavage of amyloid precursor protein (APP). This cleavage produces Aβ of varying lengths, with longer peptides like Aβ42 being more prone to aggregation than shorter peptides such as Aβ40. Of the >150 distinct, 100% penetrant PSEN1 mutations associated with ADAD, most lead to a partial or nearly complete loss of g‐secretase function, resulting in decreased production of Aβ40 and an increase in the ratio of Aβ42:Aβ40. Aggregation of Aβ peptides into amyloid plaques in the brain is a hallmark of ADAD. Method: Paros Bio is employing a gene replacement approach to normalize g‐secretase function. Using an AAV vector, Paros has successfully expressed a functional copy of PSEN1 in mouse and patient‐derived cellular models of presenilin dysfunction. Result: We have demonstrated that introduction of wildtype PSEN1 in mouse models and patient‐derived cell lines effectively normalizes g‐secretase function. Our AAV vector can be broadly distributed in brain tissue and provides attractive expression of PSEN1 . Conclusion: Paros Bio has developed a vector that enables broad expression of WT PSEN1 and is capable of normalizing g‐secretase function in in vitro and in vivo models of ADAD.